Walking in Quick Steps. Tadeusz Peiper and the Cinema (after 1945) - Wójtowicz, Aleksander ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The article deals with Tadeusz Peiper’s film writings (1947–1963). His constructivist theory was mainly concerned with the formal aspects of the cinema (color, sound). However, a very important role was played by nostalgy for harmony and community (Ferdinand Tönnies). It was articulated in the spirit similar to Martin Buber’s philosophy.